2010
DOI: 10.1159/000319596
|View full text |Cite
|
Sign up to set email alerts
|

Early Improvement in Peripheral Vascular Tone following Smoking Cessation Using Nicotine Replacement Therapy: Aortic Wave Reflection Analysis

Abstract: Objectives: Cigarette smoking induces cardiovascular pathology and worsens arterial stiffness. Arterial stiffness can be assessed noninvasively based on 2 indices: pulse-wave velocity (PWV), indicating aortic stiffness, and the augmentation index (AIx), indicating aortic wave reflection. The impact of smoking cessation (SC) with nicotine replacement therapies (NRT) on arterial stiffness remains unknown. Methods: AIx and PWV were studied prospectively (using a SphygmoCor system) in 26 long-term smokers (>10 cig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 52 publications
(54 reference statements)
0
14
0
Order By: Relevance
“…Several prospective studies using behavioral/cognitive and/or bupropion therapy have concluded that smoking cessation reduces wave reflections, whereas its effect on aortic stiffness is of less magnitude (see later) [10][11][12] . In line with these findings, Roux et al [4] demonstrated that smoking cessation reduced augmentation index, i.e. a measure of wave reflections, but not carotidfemoral pulse wave velocity, i.e.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Several prospective studies using behavioral/cognitive and/or bupropion therapy have concluded that smoking cessation reduces wave reflections, whereas its effect on aortic stiffness is of less magnitude (see later) [10][11][12] . In line with these findings, Roux et al [4] demonstrated that smoking cessation reduced augmentation index, i.e. a measure of wave reflections, but not carotidfemoral pulse wave velocity, i.e.…”
mentioning
confidence: 78%
“…Aortic stiffness depends on the level of blood pressure, and it increases as blood pressures rises. In the study of Roux et al [4] systolic blood pressure increased after smoking cessation. Although this finding seems unexpected, it is in line with previous observations [19] and it could be linked to increases in body weight after smoking cessation.…”
Section: Smoking Cessation Aortic Stiffness and Central Hemodynamicmentioning
confidence: 89%
See 3 more Smart Citations